Ammonothermal Synthesis, Optical Properties, and DFT Calculations of Mg2PN3 and Zn2PN3. Issue 52 (22nd August 2018) - Mallmann, Mathias; Maak, Christian; Niklaus, Robin; Schnick, Wolfgang
Abstract: The phosphorus nitrides, Mg2 PN3 and Zn2 PN3, are wide band gap semiconductor materials with potential for application in (opto)electronics or photovoltaics. For the first time, both compounds were synthesized ammonothermally in custom‐built high‐temperature, high‐pressure autoclaves starting from P3 N5 and the corresponding metals (Mg or Zn). Alkali amides (NaNH2, KNH2 ) were employed as ammonobasic mineralizers to increase solubility of the starting materials in supercritical ammonia through formation of reactive intermediates. Single crystals of Mg2 PN3, with length up to 30 μm, were synthesized at 1070 K and 140 MPa. Zn2 PN3 already decomposes at these conditions and was obtained as submicron‐sized crystallites at 800 K and 200 MPa. Both compounds crystallize in a wurtzite‐type superstructure in orthorhombic space group Cmc 21, which was confirmed by powder X‐ray diffraction. In addition, single‐crystal X‐ray diffraction measurements of Mg2 PN3 were carried out for the first time. To our knowledge, this is the first single‐crystal X‐ray study of ternary nitrides synthesized by the ammonothermal method. The band gaps of both nitrides were estimated to be 5.0 eV for Mg2 PN3 and 3.7 eV for Zn2 PN3 by diffuse reflectance spectroscopy. DFT calculations were carried out to verify the experimental values. Furthermore, a dissolution experiment was conducted to obtain insights into the crystallization behavior of Mg2 PN3 . Abstract : Ammonothermal synthesis : Single crystals of Mg2 PN3 and crystallites of Zn2 PN3 in the submicron‐range were synthesized in supercritical ammonia, using custom‐built high‐pressure autoclaves. Both nitrides crystallize in a wurtzite‐type superstructure and are wide‐band‐gap semiconductors. The optical band gaps were investigated by diffuse reflectance spectroscopy.